Comparison of pregnant mare serum gonadotropin products with surprising differences in protein content - Martina Lösle; Chia-Wei Lin; Jane Beil-Wagner; Markus Aebi; Thorsten Buch (Scientific Reports)
Abstract Equine chorionic gonadotropin (eCG) is a widely used hormone that synchronizes the female cycle and induces estrus in livestock. eCG is a heterodimeric glycoprotein composed of non-covalently linked α- and β-chains whose glycosylation profiles determine the in vivo activity of the hormone. The commercially available eCG products are crudely purified from the serum of pregnant mares, hence called pregnant mare serum gonadotropin (PMSG). Appropriate glycosylation of the protein is crucial for the correct binding to the receptor, receptor activation, and its half-life. The exact protein composition of the various commercial PMSG products and their specific glycosylation pattern have not been characterized so far. Therefore, we used proteomic approaches to analyse and compare four commercial PMSG products. Here we show that the examined PMSGs share a surprisingly low level of commonalities (5.5%) in protein composition among the four tested products, with serum proteins as the primary variable. Analysing the site-specific N-glycosylation, we confirmed the presence of O-acetylation of sialic acids at the structure of the glycans of eCG, which we could not find in significant amounts on human CG, suggesting that this modification is species-specific. It remains to be tested whether the O-acetylation plays an important role in the function of PMSG. However, this modification shall be considered while recombinant eCG are produced.